Community Empowerment and Sustainable Economic Improvement through Semut Island Eco-Tourism Village Program by PT Pertamina Patra Niaga Fuel Terminal Sei Siak - Syofiyardi Syofiyardi; Riyadiyanto Riyadiyanto; Siti Maisarah (Ridwan Institute, 2022)
The CSR program is a form of the company's contribution to realizing its responsibilities as regulated in Law Number 40 of 2007 concerning Limited Liability Companies. Through Community development as a CSR strategy, PT Pertamina Patra Niaga Fuel Terminal Sei Siak built an ecotourism-based tourism village on Semut Island, Pekanbaru City, Riau Province. This ecotourism village development program aims to empower the community, preserve the environment, and attract tourists, which impacts sustainable economic development. This research uses descriptive qualitative methods with documentation study and in-depth interviews. The results showed that the ecotourism-based empowerment program could contribute to environmental conservation, which increased fish, shrimp, and other biota commodities for food supplies and became an attraction for tourists to Semut Island, which would generate sustainable economic benefits. In terms of society, the Tourism Village program provides Saung Education as a gathering place to increase residents' capacity. PT Pertamina Patra Niaga Fuel Terminal Sei Siak will monitor and supervise the program's sustainability and biodiversity on Semut Island.